A new genus, Planticonsortium (Mucoromycotina), and new combination (P. tenue), for the fine root endophyte, Glomus tenue (basionym Rhizophagus tenuis) - Walker, Christopher; Gollotte, Armelle; Redecker, Dirk (Mycorrhiza, 2018)
In 1977, the fine root endophyte, originally named Rhizophagus tenuis , was transferred into the genus Glomus as G. tenue , thus positioning the species with all other known arbuscular mycorrhizal fungi ( Glomeromycota , Glomeromycotina ). Recent molecular evidence, however, places it in a different subphylum, Mucoromycotina in the Mucoromycota . No suitable genus exists in the Mucoromycotina to accommodate G. tenue , so it is moved to Planticonsortium gen. nov. as P. tenue comb. nov.